Carbon capture: advances and challenges of technologies in the energy context - Bastos de Santana, Milena; Carvalho Menezes, Gustavo; Victor Rocha Brandão, Paulo; Carvalho Castello Branco, Rafael; Norberto Araujo, Danielly; Bastos Resende, Vinícius (Latin American Journal of Energy Research, 2024)
Carbon capture has emerged as a crucial strategy to mitigate climate change, balancing economic development and environmental preservation. Focused on reducing greenhouse gases (GHG) emissions, there are technologies aimed at capturing carbon dioxide (CO2) from emitting sources before it is released into the atmosphere, enabling its storage in geological formations or its reuse in the production of high-value products, such as synthetic fuels. Combined with international climate policies, such as the Paris Agreement, and the carbon market, carbon capture complements renewable sources and promotes technological innovation. Despite the technical and economic challenges, its application is essential for a sustainable energy transition, reinforcing decarbonization and contributing to tackling climate change. This study presents a comprehensive analysis of carbon capture, utilization and storage (CCUS) technologies, addressing their potential, limitations, and role in the transition to a low-carbon economy.
Keywords: carbon capture; decarbonization; combustion; climate change; energy transition